Wage flexibility and local labour markets: homogeneity of the wage curve in Spain - Victor Montuenga; Roberto Bande; Melchor Fernandez (European Regional Science Association (ERSA), 2011)
In this paper we analyse wage flexibility in Spain and its regional differences, departing from the estimation of wage curves. Specifically, and using as the main data source the Wage Structure Survey, we proceed to estimate for each Spanish region a wage equation, which explains observed wage received by workers to a group of personal and job characteristics, as well as the unemployment rate. This analysis allows to test hypothesis concerning the possible changes that may have occurred in each region in the degree of wage flexibility between the two years considered in the Survey. Also, we test the existence of regional differences in the degree of wage flexibility, which may have an important influence in the evolution of regional unemployment, given its impact on the ability of the local labour market to absorb negative shocks. The paper also allows to analyse the variability of the wage flexibility estimation with respect to the dependent variable, which could explain opposite results in the existing literature
Keywords: 330